Unilateral nevoid acanthosis nigricans: Uncommon variant of a common disease - Anupam Das; Sabari Bhattacharya; Piyush Kumar; Tirthankar Gayen; Kunal Roy; Nilay K Das; Ramesh C Gharami (Wolters Kluwer Medknow Publications, 2014)
Acanthosis nigricans (AN) is a fairly common dermatosis characterized by hyperpigmented velvety plaques, having a predilection for the intertriginous areas. We herein present a case of unilateral nevoid acanthosis nigricans over the left lateral chest, in an adult male. The rarity of documentation of this entity in the world literature prompted us to report the case.